Pengaruh Literasi Keuangan Syariah dan Pendapatan Terhadap Minat Menabung di Bank Syariah Indonesia Cabang Palur (Survei pada Pedagang Pasar Palur) - Norizza Dana Norisma; Suprihatmi SW (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to analyze the influence of Sharia financial literacy and income on savings interest at the Palur Branch of Bank Syariah Indonesia. The data used in this study is quantitative. Primary data sources were used. Data collection in this study used questionnaires distributed to respondents. The sample consisted of 70 traders in the Palur market, drawn using the Slovin formula. The sampling technique used was purposive sampling, or sampling based on specific characteristics. The analytical methods used in this study were descriptive analysis, multiple linear regression analysis, t-test, F-test (model fit test), and coefficient of determination (R2) test. The t-test results of the study indicate that Sharia financial literacy significantly influences savings interest at Bank Syariah Indonesia, Palur Branch, with a p-value of 0.000 <0.05, and income significantly influences savings interest at Bank Syariah Indonesia, Palur Branch, with a p-value of 0.000 <0. The F-test results indicate that the regression model used in this study is appropriate, with a p-value of <0.05. The coefficient of determination (R2) test indicates that the independent variable contributes 71.8% to the dependent variable, with the remaining 28.2% (100-71.8%) explained by other variables outside the model